Elastic properties of compressed cryocrystals in a deformed atom model - Gorbenko, Ie.Ie.; Zhikharev, I.V.; Troitskaya, E.P.; Chabanenko, Val.V.; Pilipenko, E.A. (Физика низких температур, 2013)
A model with deformed atom shells is built to investigate the elastic properties of rare-gas crystals Ne and Kr
under high pressure. It is shown that the observed deviation from the Cauchy relation cannot be adequately reproduced
with taking into account of only the many-body interaction. The individual pressure dependence of is
a result of competition of the many-body interaction and the quadrupole interaction associated with the quadrupoletype deformation of electron shells of the atoms during the displacements of the nuclei. Each kind of interaction
makes a strongly pressure dependent contribution to . In the case of Ne and Kr, contributions of these
interactions are compensated to the good precision, providing being almost constant against pressure.